Effect of homogenization on microstructure evolution and mechanical properties of aged Mg-Nd-Sm-Zn-Zr alloy. (15th December 2021) - Ma, Tao; Zhao, Sicong; Wang, Liping; Wang, Zhiwei; Guo, Erjun; Feng, Yicheng; Liu, Dongrong; Wu, Changtong; Li, Jingfang
Abstract: As an indispensable pre-treatment for aging, homogenization treatment has a significant effect on precipitation behavior of the Mg-RE alloys. Herein, the influence of homogenization temperature on the microstructure evolution and mechanical performance of a novel Mg-2.0Nd-2.0Sm-0.4Zn-0.4Zr (wt.%) alloy has been studied systematically. The results indicated that the as-cast alloy was mainly composed of α -Mg matrix, β -Mg12 (Nd, Sm, Zn) phase and Zr-containing particles. Upon increasing the homogenization temperature from 500 °C to 525 °C for 8 h, the average grain size of as-homogenized alloy increased from 76 μ m to 156 μ m, and the content of β phase decreased gradually. It was worth noting that the homogenization temperature exceeded 515 °C, the β phase at the grain boundaries was completely dissolved. After aging at 200 °C for 18 h, numerous of plate-like β ′ phases were observed in α -Mg matrix. The rise in homogenization temperature was conducive to nucleation and growth of the β ′ phase. However, excessive homogenization temperature significantly coarsened grain size. The aged alloy under homogenization treatment at 515 °C for 8 h achieved optimal mechanical properties. The values of ultimate tensile strength, yield strength and elongation were 261 MPa, 154 MPa and 5.8%, respectively. The fracture mode of the aged alloy mainly exhibited a typical transgranular cleavage fracture.